1990
DOI: 10.1111/j.2044-8309.1990.tb00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowing what to think by knowing who you are: Self‐categorization and the nature of norm formation, conformity and group polarization*

Abstract: We contrast two theoretical approaches to social influence, one stressing interpersonal dependence, conceptualized as normative and informational influence (Deutsch & Gerard, 1955), and the other stressing group membership, conceptualized as selfcategorization and referent informational influence (Turner, Hogg, Oakes, Reicher & Wetherell, 1987). We argue that both social comparisons to reduce uncertainty and the existence of normative pressure to comply depend on perceiving the source of influence as belonging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
428
2
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 624 publications
(456 citation statements)
references
References 36 publications
15
428
2
11
Order By: Relevance
“…Research has repeatedly demonstrated that social identity concerns and beliefs (which refer to individuals' definition of the self in terms of group-defining attributes) play a vital role in shaping how recipients respond to information about the message source when processing messages (Abrams et al 1990, David and Turner 1996, Mackie et al 1990, Wood 2000. Social identity theory is thus an ideal bridge between the two literatures we integrate: the literature concerning individual motivations driving online contribution (which emphasizes identity motives) and the literature associating the content of these contributions with community-level outcomes (i.e., peer recognition and product sales).…”
Section: Research Contextmentioning
confidence: 99%
“…Research has repeatedly demonstrated that social identity concerns and beliefs (which refer to individuals' definition of the self in terms of group-defining attributes) play a vital role in shaping how recipients respond to information about the message source when processing messages (Abrams et al 1990, David and Turner 1996, Mackie et al 1990, Wood 2000. Social identity theory is thus an ideal bridge between the two literatures we integrate: the literature concerning individual motivations driving online contribution (which emphasizes identity motives) and the literature associating the content of these contributions with community-level outcomes (i.e., peer recognition and product sales).…”
Section: Research Contextmentioning
confidence: 99%
“…Employing a variety of related theories such as social proof, social comparison, conformity and social norms, herding behavior, and information cascades, researchers have demonstrated that people are greatly influenced by the behaviors of others (Asch 1951, Banerjee 1992. Notably, social influence is most effective when uncertainty is high (Wooten and Reed 1998) and when following the lead of others that are perceived to be close, similar, or aspirational (Cialdini 2001, p. 140;Festinger 1954;Abrams et al 1990;Burn 1991). Thus, we will focus on customer uncertainty and homophily as critical factors in the influence process.…”
Section: Introductionmentioning
confidence: 99%
“…This effect of religious identity operates even when an individual does not attend church regularly, since (i) other mechanisms such as personal networks and parental socialization provide enough information about beliefs and preferences among religious individuals, and (ii) the self-identification mechanism works even in absence of social control (Abrams et al 1990).…”
mentioning
confidence: 99%